Documentary theater: in search of its historical matrices and theoretical foundations - Nanci, Ana Carolina Angrisani Fiorentino (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2024)
In this article, the author explores the historical matrices and foundations of documentary theater, starting from the artistic manifestations of agitation and propaganda, known as agitprop in the context of the Russian-Soviet revolution and the works of Erwin Piscator at the beginning of the 20th century. Highlighting the relationships between art and revolution that existed in the period and their reverberations in Brazil, manifested in the theater of Augusto Boal among others.